Developing Standards for PSMA 2009 Implementing Port and Its Implementation in Indonesia - Solihin, Akhmad; Darmawan, Darmawan; Sondita, Muhammad F.A.; Purbayanto, Ari (Indonesian Journal of International Law, 2024)
The ratified countries of PSMA 2009 are mandated to determine their implementing port without specifying any particular standards. The presence of port standards will ensure the effectiveness of services in preventing and eradicating IUU Fishing. Therefore, standards are needed to optimize the main objectives of the 2009 PSMA, especially in Indonesia, an archipelagic country with diverse fishing port classes and different management systems between general cargo ports and fishing ports. The objectives of this research are (1) to develop service standards for ports implementing PSMA 2009 and (2) to examine the readiness of ports implementing PSMA 2009 to prevent IUU fishing. This research uses content analysis and literature review methods. The results of this study reveal that Indonesia has legally adopted the 2009 PSMA, but there are two port state regimes that prevent and reduce IUU fishing such as Port State Measures and Port State Control. The service standards that must be met by ports designated to implement PSMA 2009 are (1) application services, including service officers receiving application letters and risk analysis officers, and (2) inspection services, including trained officers, authorized officers, English-speaking officers, inter-agency coordination mechanisms, and officer identity. While Benoa General Cargo/Public Port is ready to implement PSMA 2009, its fishing port still needs improvement.